International trade 1974/75 - general agreement and tariffs and trade (Geneva, 1975)
The year 1974 and the first half of 1975 have seen the culmination of a world-wide inflationary wave, coinciding with a deep recession spreading from industrial countries to other parts of the world. Both the inflation and the recession are of a magnitude unprecedented in post history.
Includes bibliographical references
hza 29/01/2019
Loans
Keywords: Commerce; international trade; Trade agreements